Assessment of Professional Values and Organizational Commitment among Nurses Working at Bharatpur Hospital, Chitwan, Nepal - Sapkota, Devi Kumari; Ranabhat, Punam Kumari Sharma; Bhusal, Mina Kumari; Regmi, Kamala (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Nurses play a vital role in the provision of healthcare internationally. Nurses’ decision-making and professional growth stem from their professional values; while organizational commitment of nurses closely connected to the productivity and quality of care provided by healthcare institutions. A study aimed to assess the professional values and organizational commitment among nurses working at Bharatpur Hospital, Chitwan, Nepal. Method: A descriptive cross-sectional study carried out among 120 nurses of Bharatpur hospital. Proportionate quota sampling technique used to select the sample from various departments i.e medical, surgical, ICU, pediatrics, orthopedics including spinal and post-operative. Data collection was done using 5-point Likert scale to assess the professional values in five domain; caring, trust, professionalism, justice and integrity and to assess the organizational commitment in three domain; affective, continuance and normative. Self-administered questionnaire technique used to collect the data from nurses. The data was analyzed in Statistical Package for the Social Science (SPSS) version 26 using descriptive and inferential statistics. Result: The finding revealed that more than half (58.3%) of nurses’ work experience was within 1-5 years. The overall mean score of professional values was 93.94±13.12 among nurses. The highest mean scores in caring and integrity domain that were 20.7(±3.54) and 20.7(±3.38) respectively. Almost half of nurses (50.8%) had higher professional values. Similarly, the mean score was 47.5±6.55 on organizational commitment and high mean percent (68.3) in affective domain. Only 47.5% nurses had higher organizational commitment. There was significant association between leadership style and professional values (p=0.021). Educational level was significantly associated with organizational commitment (p=0.041). A positive correlation was found between professional values and organizational commitment(r=0.201, p=0.028). Conclusion: The study concluded that the need for healthcare institutions to prioritize ethical training and supportive leadership seems importance to foster a dedicated nursing workforce and ultimately improve overall healthcare outcomes.